Characterization of muscle mass, strength and mobility of critically ill patients with SARS-CoV-2 pneumonia: Distribution by sex, age, days on mechanical ventilation, and muscle weakness - Silva-Gutiérrez, Alexis; Artigas-Arias, Macarena; Alegría-Molina, Andrea; Guerra-Vega, Pablo; Navarrete, Pablo; Venegas, Ángela; Montecinos, Carlos; Vásquez, Lorena; Moraga, Karen; Rubilar, César; Villagrán, Germán; Parada, Rodrigo; et al. (Frontiers in Physiology, 2023)
Objective: Quantify and categorize by sex, age, and time spent on mechanical ventilation (MV), the decline in skeletal muscle mass, strength and mobility in critically ill patients infected with SARS-CoV-2 and requiring mechanical ventilation while at intensive care unit (ICU). Design: Prospective observational study including participants recruited between June 2020 and February 2021 at Hospital Clínico Herminda Martin (HCHM), Chillán, Chile. The thickness of the quadriceps muscle was evaluated by ultrasonography (US) at intensive care unit admission and awakening. Muscle strength and mobility were assessed, respectively, through the Medical Research Council Sum Score (MRC-SS) and the Functional Status Score for the Intensive Care Unit Scale (FSS-ICU) both at awakening and at ICU discharge. Results were categorized by sex (female or male), age (<60 years old or ≥60 years old) and time spent on MV (≤10 days or >10 days). Setting: Intensive care unit in a public hospital. Participants: 132 participants aged 18 years old or above (women n = 49, 60 ± 13 years; men n = 85, 59 ± 12 years) admitted to intensive care unit with a confirmed diagnosis of severe SARS-CoV-2 and requiring MV for more than 48 h were included in the study. Patients with previous physical and or cognitive disorders were excluded. Interventions: Not applicable. Results: Muscle thickness have significantly decreased during intensive care unit stay, vastus intermedius (−11%; p = 0.025), rectus femoris (−20%; p < 0.001) and total quadriceps (−16%; p < 0.001). Muscle strength and mobility were improved at intensive care unit discharge when compared with measurements at awakening in intensive care unit (time effect, p < 0.001). Patients ≥60 years old or on MV for >10 days presented greater muscle loss, alongside with lower muscle strength and mobility. Conclusion: Critically ill patients infected with SARS-CoV-2 and requiring MV presented decreased muscle mass, strength, and mobility during their intensive care unit stay. Factors associated with muscle mass, such as age >60 years and >10 days of MV, exacerbated the critical condition and impaired recovery.